Corrigendum to “Developing mathematics teaching materials using maritime context for higher-order thinking in junior high school,” [Journal on Mathematics Education, Volume 15, No. 1, 2024, pp. 173-190] - Malalina; Putri, Ratu Ilma Indra; Zulkardi; Hartono, Yusuf (Journal on Mathematics Education, 2024)
The authors express regret regarding the first author's affiliation with the Mathematics Education Department, Universitas Sriwijaya, Palembang, Indonesia. They extend their apologies for any inconvenience this may have caused.